INTERNAL GOVERNANCE MECHANISMS AND FIRM PERFORMANCE: THE CASE OF VIETNAM - Nguyen, Tien Thong (PEOPLE: International Journal of Social Sciences, 2021)
Good corporate governance would contribute to the sustainable development of the economy. Better corporate governance is supposed to lead to better corporate performance and expropriation of controlling shareholders is supposed to be prevented. Studies of impacts of corporate governance on organizational performance had started since 1990s. Vietnam is a developing country with an underdeveloped financial market and week regulatory principles. Therefore, an approach of internal mechanism is supposed to be a better way to improve the quality of corporate governance than external mechanisms. Two internal governance mechanisms (IGMs) are examined in the relationship with corporate performance in this study include (1) Ownership structure and (2) Board of Directors. The results shows that largest shareholder, controlled directors and duality have negative impacts on firm performance while family ownership, board of director ownership, institutional ownership and foreign ownership have positive impacts on firm performance. The study makes theoretical and empirical contribution to the understanding for the development of an effective corporate governance framework in Vietnamese market.